Sum of Squares Polynomial Approximate Dynamic Programming for the Ergodic Problem - Hexner, Gyorgy (IEEE transactions on automatic control, 2025)
The purpose of this note is to extend the approximate dynamic programming (ADP) method to the infinite time stochastic optimal control (ergodic) problem. It is also shown that a modification of the basic algorithm solves the output feedback problem. The ADP solution of the ergodic problem differs in significant ways from its deterministic counterpart.